Collisions, Cosmic Radiation and the Colors of the Trojan Asteroids - Melita, Mario Daniel (2009)
The Trojan asteroids orbit about the Lagrangian points of Jupiter and the residence times about their present location are very long for most of them. If these bodies originated in the outer Solar System, they should be mainly composed of water ice, but, in contrast with comets, all the volatiles close to the surface would have been lost long ago. Irrespective of the rotation period, and hence the surface temperature and ice sublimation rate, a dust layer exists always on the surface. We show that the timescale for resurfacing the entire surface of the Trojan asteroids is similar to that of the flattening of the red spectrum of the new dust by solar-proton irradiation. This, if the cut-off radius of the size distribution of the impacting objects is between 1mm and 1m and its slope is -3, for the entire size-range. Therefore, the surfaces of most Trojan asteroids should be composed mainly of unirradiated dust